Enhanced anxiety in the male offspring of sires that self‐administered cocaine. (29th April 2015) - White, Samantha L.; Vassoler, Fair M.; Schmidt, Heath D.; Pierce, R. Christopher; Wimmer, Mathieu E.
Abstract: We previously showed that paternal cocaine exposure reduced the reinforcing efficacy of cocaine in male offspring. Here, we sought to determine whether paternal cocaine experience could also influence anxiety levels in offspring. Male rats were allowed to self‐administer cocaine (controls received saline passively) for 60 days and then were bred with naïve females. Measures of anxiety and cocaine‐induced anxiogenic effects were assessed in the adult offspring. Cocaine‐sired male offspring exhibited increased anxiety‐like behaviors, as measured using the novelty‐induced hypophagia and defensive burying tasks, relative to saline‐sired males. In contrast, sire cocaine experience had no effect on anxiety‐like behaviors in female offspring. When challenged with an anxiogenic (but not anorectic) dose of cocaine (2.5 mg/kg, i.p.), anxiety‐like behavior was enhanced in all animals to an equal degree regardless of sire drug experience. Since anxiety and depression are often co‐morbid, we also assessed measures of depressive‐like behavior. Sire cocaine experience had no effect on depression‐like behaviors, as measured by the forced swim task, among male offspring. In a separate group of naïve littermates, select neuronal correlates of anxiety were measured. Male offspring of cocaine‐experienced sires showed increased mRNA and protein expression of corticotropin‐releasing factor receptor 2 in the hippocampus. Together, these results indicate that cocaine‐experienced sires produce male progeny that have increased baseline anxiety, which is unaltered by subsequent cocaine exposure. Abstract : Paternal cocaine exposure was recently shown to reduce the reinforcing efficacy of cocaine in male offspring. Here, we found that paternal cocaine experience could also influence anxiety levels in progeny. Male offspring of cocaine‐experienced sires exhibited increased anxiety‐like behaviors, as measured using the novelty‐induced hypophagia and defensive burying tasks, relative to control. When challenged with an anxiogenic dose of cocaine (2.5 mg/kg, i.p.), anxiety‐like behavior was enhanced in all animals to an equal degree regardless of sire drug experience.